Modeling the Impact of Cultural Education Policies on Literacy Rates Using Numerical Differential Equations - Sahani, Suresh Kumar; Prasad, Kripa Sindhu (Journal of Posthumanism, 2023)
This research focuses on the effects of culture-inclusive education—especially for marginalized communities—on national literacy rates, looking into the dynamics over long periods. It applies numerical differential equations to estimate literacy changes over time in response to specific educational policies like bilingual education, incorporation of local curricula, or culturally relevant teaching methods. Given the dataset from Sub-Saharan Africa, Latin America, and South Asia, this research builds a dynamic system that captures how policy changes impact literacy rate trajectories. Euler and Runge-Kutta methods results strongly support the non-linear, underscored positive impact of inclusive cultural policies. UNESCO and World Bank datasets perform well in estimating parameters for the model’s calibration, ensuring reliability. It is shown that culturally informed education policies can transform literacy dynamics in diverse linguistic regions. This evidence is critical for educational policymakers and development agencies working to advance culturally responsive frameworks in global literacy initiatives.